Computational tools for signal processing of human gait - Carvalho, André (2019)
Human locomotion control is a complex task affected by age and health conditions disturbing the somatosensorial inputs (e.g. Ménièr’s syndrome, diabetes) or the performance of the muscle-skeletal system (e.g. hip transplant)